PENGARUH PEMILIHAN KANTOR AKUNTAN PUBLIK DAN KARAKTERISTIK MANAJEMEN TERHADAP MANAJEMEN LABA - Prakoso, Ganang; Purwanto, Agus (Diponegoro Journal of Accounting, 2017)
This study aimed to analyze the effect of size auditor and board characteristic on earning management. This study used the entire population of the manufacture sector companies listed on the Indonesia Stock Exchange in 2012 until 2015. Sampling was done by purposive sampling technique and obtained samples used in this study were 47 companies. The method of analysis used in this study is multiple regression. This study used the dependent variable (earning management) and the independent variables (auditor size, size of commissioner, board size, managerial ownership, independent of commissioner,  board of director tenure, board of director interlock and size of audit committee). The result showed that boards of director interlock have significantly positive effect against earnings management. Auditor size, size of commissioner, managerial ownership, independent of commissioner, board of director tenure, board of director interlock and size of audit committee are not significant against earning management. Board size has significantly negative effect on earning management.